2018
DOI: 10.1371/journal.pone.0190482
|View full text |Cite
|
Sign up to set email alerts
|

Local chatter or international buzz? Language differences on posts about Zika research on Twitter and Facebook

Abstract: BackgroundWhen the Zika virus outbreak became a global health emergency in early 2016, the scientific community responded with an increased output of Zika-related research. This upsurge in research naturally made its way into academic journals along with editorials, news, and reports. However, it is not yet known how or whether these scholarly communications were distributed to the populations most affected by Zika.Methodology/Principal findingsTo understand how scientific outputs about Zika reached global and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
11
0
6
Order By: Relevance
“…It has been reported that Public Information Officers who were monitoring social media felt better prepared for Zika and were more satisfied with their crisis management since social media facilitates the spread of both accurate and false information [37]. Understanding these media effects is essential to communicate public health information and engage different populations in the community [38]. Above all, the need to access social media to gain knowledge about the debilitating virus clearly demonstrates the lack of satisfaction with then available official information about Zika.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Public Information Officers who were monitoring social media felt better prepared for Zika and were more satisfied with their crisis management since social media facilitates the spread of both accurate and false information [37]. Understanding these media effects is essential to communicate public health information and engage different populations in the community [38]. Above all, the need to access social media to gain knowledge about the debilitating virus clearly demonstrates the lack of satisfaction with then available official information about Zika.…”
Section: Discussionmentioning
confidence: 99%
“…Por essa razão, o Altmetric coleta dados bastante incompletos no Facebook que dão a impressão de que a rede é pouco relevante para a atenção social de informações científicas, sendo vista, portanto, como de pouco valor por acadêmicos do mundo todo. A identificação de métodos alternativos, como a análise de artigos compartilhados em postagens públicas do API do Facebook (Enkhbayar; Alperin, 2018), traz algumas possibilidades interessantes de pesquisa futura.…”
Section: Discussionunclassified
“…Apesar de grande uso do Facebook por editores de revistas científicas brasileiras, como mencionado na seção anterior, há importantes limitações para o uso de dados dessa rede social para gerar dados altmétricos, sendo focalizado neste artigo o provedor Altmetric.com, mais usado e analisado entre especialistas em altmetria. Análise de Enkhbayar e Alperin (2018) sugere que os dados que o Altmetric.com captura do Facebook são inferiores à atividade que ocorre na rede social para compartilhar artigos científicos, como mostram dados coletados a partir do API do Facebook. É fato que a empresa britânica que produz esses indicadores alternativos, a Altmetric.com, apenas rastreia o compartilhamento de links de artigos científicos em postagens públicas de grupos ou instituições.…”
Section: As Limitações Da Altmetriaunclassified
See 1 more Smart Citation
“…It has been reported that Public Information Officers who were monitoring social media felt better prepared for Zika and were more satisfied with their crisis management since social media facilitates the spread of both accurate and false information [31]. Understanding these media effects is essential to communicate public health information and engage different populations in the community [32]. Above all, the need to access social media to gain knowledge about the debilitating virus clearly demonstrates the lack of satisfaction with then available official information about Zika.…”
Section: Discussionmentioning
confidence: 99%